REDUCTION OF ALCOHOL CONSUMPTION CAN DECREASE HOME MORNING BLOOD PRESSURE IN MALE HYPERTENSIVE PATIENTS-OSAKE STUDY. (April 2021) - Akagi, Yuya; Kabayama, Mai; Tamatani, Michio; Tomita, Jun; Takiuchi, Shin; Yamamoto, Koichi; Sugimoto, Ken; Rakugi, Hiromi; Kamide, Kei
Abstract : Objective: Excess alcohol consumption is supposed to be a strong risk of blood pressure (BP) elevation, therefore the reduction of number of heavy drinkers is an important issue for health promotion. In previous studies, few studies have examined the effectiveness of reduced alcohol intake on BP by improving drinking habits. The aim of this study is to investigate the association between reduced alcohol consumption and changes in home morning BP in male hypertensive patients. Design and method: This research was conducted as part of OSAKE Study. The OSAKE study (a randomized controlled trial of saving alcohol amount program for keeping optimal blood pressure control in patients with hypertension) provides outpatient health guidance intervention and verifies its effectiveness on BP reduction. The subjects were 51 men who completed a six-month health guidance intervention or control period. Detailed alcohol consumption per week was inquired and converted to pure alcohol (g). A home BP auto measuring apparatus with auto data communicating system by internet was distributed to patients. To investigate the relationship between changes in alcohol consumption and BP reduction (δSBP, δDBP), multiple regression analysis adjusted for changes in room temperature (δT), the correlation of baseline BP with alcohol consumption was performed.δ Results: Mean age in study participants was 64 ± 7.6 years old. After 6 months from baseline, the weekly alcohol consumption decreased significantly from 423.2 ± 288.8 g to 330.2 ± 243.9 g (p < 0.01). Regarding weekly and monthly BP average both systolic BP (SBP) and diastolic BP (DBP) significantly decreased (1week SBP: 142 ± 10.3 to 138.9 ± 13, DBP: 88.1 ± 8.3 to 85.1 ± 9.8, 1 month SBP: 141.3 ± 10.1 to 138.2 ± 12.2, DBP: 87.9 ± 8.4 to 84.8 ± 9.4, respectively p < 0.05). As a result of multiple regression analysis, δalcohol consumption was significantly associated with both δSBP and δDBP for one week and one month (p < 0.05). For covariates, δT and δγGTP were also significantly associated with BP reduction. Conclusions: It may be effective for lowering home morning BP to improve drinking habits in male hypertensive patients.